Comparative analysis of the complete genome sequence of the plant growth–promoting bacterium Bacillus amyloliquefaciens FZB42 - Chen, Xiao Hua; Koumoutsi, Alexandra; Scholz, Romy; Eisenreich, Andreas; Schneider, Kathrin; Heinemeyer, Isabelle; Morgenstern, Burkhard; Voss, Björn; Hess, Wolfgang R; Reva, Oleg; Junge, Helmut; Voigt, Birgit; et al. (Nature biotechnology, 2007)
Bacillus amyloliquefaciens FZB42 is a Gram-positive, plant-associated bacterium, which stimulates plant growth and produces secondary metabolites that suppress soil-borne plant pathogens. Its 3,918-kb genome, containing an estimated 3,693 protein-coding sequences, lacks extended phage insertions, which occur ubiquitously in the closely related Bacillus subtilis 168 genome. The B. amyloliquefaciens FZB42 genome reveals an unexpected potential to produce secondary metabolites, including the polyketides bacillaene and difficidin. More than 8.5% of the genome is devoted to synthesizing antibiotics and siderophores by pathways not involving ribosomes. Besides five gene clusters, known from B. subtilis to mediate nonribosomal synthesis of secondary metabolites, we identified four giant gene clusters absent in B. subtilis 168. The pks2 gene cluster encodes the components to synthesize the macrolactin core skeleton.